2003
DOI: 10.1124/jpet.103.061002
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Cannabidiol, a Nonpsychoactive Cannabinoid, on Human Glioma Cell Lines

Abstract: Recently, cannabinoids (CBs) have been shown to possess antitumor properties. Because the psychoactivity of cannabinoid compounds limits their medicinal usage, we undertook the present study to evaluate the in vitro antiproliferative ability of cannabidiol (CBD), a nonpsychoactive cannabinoid compound, on U87 and U373 human glioma cell lines. The addition of CBD to the culture medium led to a dramatic drop of mitochondrial oxidative metabolism [3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H tetrazolium bromide t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
212
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(238 citation statements)
references
References 34 publications
13
212
0
2
Order By: Relevance
“…However, in line with our data cannabidiol has been reported to exert several of its effects, including modulation of cytokine release and macrophage chemotaxis [11] as well as antiproliferative [12] and proapoptotic properties [13] in a cannabinoid receptor-dependent manner. One possible explanation for the discrepancy between the low receptor affinity and the apparent involvement of cannabinoid receptors in cannabidiol-mediated effects may be given by cannabidiol´s inhibitory action on fatty acid amidohydrolase activity that confers release of anandamide and increased receptor-mediated signalling by this endocannabinoid [16][17][18].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, in line with our data cannabidiol has been reported to exert several of its effects, including modulation of cytokine release and macrophage chemotaxis [11] as well as antiproliferative [12] and proapoptotic properties [13] in a cannabinoid receptor-dependent manner. One possible explanation for the discrepancy between the low receptor affinity and the apparent involvement of cannabinoid receptors in cannabidiol-mediated effects may be given by cannabidiol´s inhibitory action on fatty acid amidohydrolase activity that confers release of anandamide and increased receptor-mediated signalling by this endocannabinoid [16][17][18].…”
Section: Discussionsupporting
confidence: 79%
“…Although cannabidiol displays a low affinity to CB 1 and CB 2 receptors [10], several effects of cannabidiol including modulation of cytokine release and macrophage chemotaxis [11], antiproliferative [12] as well as proapoptotic properties [13] have been shown to be mediated via CB 1 and/or CB 2 receptors. In other investigations, cannabidiol has even been reported to display antagonistic effects on CB 1 and CB 2 receptor [14], as well as synergistic effects on THC-mediated hypoactivity, hypothermia and impairment of spatial memory [15].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, when the same in vitro assay was performed on normal fibroblasts (WI-38 human lung fibroblasts) CBD exerted no statistically significant effect on sphingomyelin hydrolysis. Furthermore, the antitumor effect of CBD has been shown to be independent on the production of ceramide in human glioma cells (but was associated with a fall in mitochondrial potential; see below) [83] and thus it remains unclear as to whether or not CBD acts directly on the ceramide pathway. …”
Section: Effects On Enzymes Controlling Ceramidementioning
confidence: 99%
“…The authors also showed for the first time that the antiproliferative effect of CBD was correlated to induction of apoptosis, as determined by cytofluorimetric analysis and single-strand DNA staining, which was not reverted by cannabinoid and vanilloid receptor antagonists. 109 CBD also caused apoptosis in human myeloblastic leukemia cells. 110 In addition, CBD inhibits the migration of U87 human glioma cells in vitro and this effect was also not antagonized by either selective CB 1 or CB 2 receptor antagonists.…”
Section: Anticancer Actionmentioning
confidence: 99%